Splanchnic oximetry in small for gestational age neonates in relation to prenatal Doppler study - Jesús Fuentes Carballal; Alejandro Avila-Alvarez; María Taboada Perianes; Soledad Martínez Regueira; Jose Luis Fernández Trisac (Elsevier, 2020)
Introduction: Among small for gestational age neonates, foetal Doppler enables the identification of placental insufficiency aetiology and the classification of severity in small for gestational age neonates. There are studies that associate the Doppler data with alterations in the intestinal flow of the newborn, but its relationship with intestinal oximetry has been little studied. Objective: To assess whether there is a relationship between prenatal Doppler data and abdominal oximetry in small for gestational age neonates. Material and methods: A prospective observational study carried out on neonates >32 weeks with a birth weight <P10. The severity of placental insufficiency was classified according to prenatal Doppler criteria. Splanchnic oximetry was monitored during the first three days of life and a comparative analysis of the oximetry data was performed according to the prenatal Doppler alteration severity. Results: A total of 53 patients were evaluated. Significant differences were observed in the mean regional oximetry (rSO2) between patients with moderate or severe placental failure and those with normal or slightly altered prenatal Doppler: 42 ± 10 vs. 71.3 ± 10 (P < .001). These differences were maintained during the first 3 days of life. Standard patterns of splanchnic oximetry were identified depending on the degree of placental insufficiency. Conclusions: There is a correlation between the foetal Doppler and the splanchnic oximetry pattern during the first days of life. Neonates with moderate or severe placental insufficiency have more altered abdominal oximetry patterns, making it a useful technique to evaluate the degree of placental insufficiency and the risk of oral intolerance in small for gestational age neonates. Resumen: Introducción: El estudio del doppler foetal permite identificar la etiología placentaria y clasificar su gravedad en aquellos neonatos pequeños para la edad gestacional. Existen estudios que relacionan estos datos doppler con alteraciones en el flujo intestinal del recién nacido, pero su relación con los datos de oximetría intestinal ha sido poco estudiada. Objetivo: Evaluar si existe relación entre los datos doppler prenatales y los datos de oximetría abdominal en los niños pequeños para su edad gestacional. Material y métodos: Estudio prospectivo observacional en neonatos > 32 semanas con un peso al nacer < P10. Se clasificó la gravedad de la insuficiencia placentaria según criterios de doppler prenatal. Se monitorizó la oximetría esplácnica durante los 3 primeros días de vida y se realizó un análisis comparativo de los datos oximétricos según la afectación doppler prenatal. Resultados: Se evaluaron 53 pacientes. Se observaron diferencias significativas en la rSO2 media entre los pacientes con fallo placentario moderado o grave y aquellos con doppler prenatal normal o levemente alterado: 42 ± 10 vs. 71,3 ± 10 (p < 0,001). Estas diferencias se mantuvieron durante los 3 primeros días de vida. Se identificaron patrones tipo de oximetría esplácnica según el grado de insuficiencia placentaria. Conclusiones: Existe correlación entre el doppler foetal y el patrón de oximetría esplácnica durante los primeros días de vida. Los neonatos con insuficiencia placentaria moderada o grave presentan unos registros de oximetría abdominal más alterados, por lo que podría ser una técnica útil para evaluar el grado de insuficiencia placentaria y el riesgo de intolerancia oral en los neonatos pequeños para la edad gestacional.